Gamifying Online Tests to Promote Retrieval-Based Learning - Petrovic-Dzerdz, Maristela (International Review of Research in Open and Distributed Learning, 2019)
Recent findings have provided strong evidence that retrieval-based learning is an effective strategy for enhancing knowledge retention and long-term meaningful learning, but it is not a preferred learning strategy for the majority of students. The present research analyzes the application of learning gamification principles in online, open-book, multiple-choice tests in order to motivate students to engage in repeated retrieval-based learning activities. The results reveal a strong positive correlation between the number of successful retrieval attempts in these tests that cover content from the course textbook, and long-term knowledge retention as demonstrated in a live, final, closed-book, cumulative exam consisting of multiple-choice, labeling, definitions, and open-ended questions covering the content of both textbook readings and lectures. The presented results suggest that online, open-book tests designed using gamification principles, even when covering partial course content and one type of questions, are an effective strategy for using educational technology to motivate students to repeatedly engage in retrieval-based learning activities and improve long-term knowledge retention, regardless of the course delivery mode.